Research landscape and trends in corporate foresight - Chichorro, E. (2022)
Corporate Foresight (СF) gains increasing research interest as an efficient decision-making tool in the face of growing market uncertainty. We carried out a bibliometric analysis of the CF literature published between 2001 and 2021. The results of bibliometric analysis propose in which journals researchers should publish their papers to obtain more citations, which to cite, which keywords to use, and which references to explore. This allows managers, researchers, and practitioners to gain in-depth knowledge of CF literature.